Young and very young stars in NGC 3372, the Carina nebula - Tapia, M. (2004)
Results are presented of a large-scale imaging photometric study of the stellar population in the northern part of NGC 3372 with a w avelength co verage from 0.33 to 2.5 µm. All observations were made at Las Campanas Observatory . The sizes of the three stellar clusters, Tr 14, Tr 15 and Tr 16, were determined b y means of star counts. Two-colour and colour-magnitude diagrams are presented and analyzed for eac h individual cluster. The three clusters were found to b e at a similar distance from the Sun, < d > = 2 . 7 kpc, but with very large scatter in both A V and d . suggesting drastic variations in intracluster dust densit y . Dust particle size distribution variations are eviden t resulting in wide variations in extinction law. We determined ages bet ween 3 and 60 million years for Tr 15 and bet ween less than 1 and 6 million years for Tr 14 and Tr 16. The Tr 14 cluster is partially em bedded in a dense molecular cloud that extends to wards the south west reaching its highest densit y some three arcmin from the cluster nucleus. The ric h UV field created b y the Tr14 stars ionizes most of the visible HI I region in its vicinit y and most of the radio HI I region Car I. Deep J H K images of the Car I region reveal the presence of a young, em bedded stellar population that includes several O9–B0 stars and an ultracompact HI I region.